ChemInform Abstract: Structure and Physical Properties of Single Crystal PrCr2Al20 and CeM2Al20 (M: V, Cr): A Comparison of Compounds Adopting the CeCr2Al20 Structure Type. Issue 5 (13th February 2013) - Kangas, Michael J.; Schmitt, Devin C.; Sakai, Akito; Nakatsuji, Satoru; Chan, Julia Y.
Abstract Crystals of LnTi2Al20 (Ln: La—Pr, Sm, Yb), LnV2Al20 (Ln: La—Pr, Sm), and LnCr2Al20 (Ln: La—Pr, Sm, Yb) are prepared from the elements by the flux growth method (alumina crucibles, 1423 K, slow cooling to 1023 K).